La universidad: su misión histórica y su deuda con la sociedad del siglo XXI - Gómez M., Patricia (Revista Hospital Clínico Universidad de Chile, 2009)
The principal and basic mission of the university is to fulfill the requirements and demands of the community it serves. We are currently living a period which is both, fascinating but also very worrisome. During the last decades, amazing changes have taken place in the world –especially in the telecommunications and transportation areas. Internet, globalization and extreme liberalism applied indiscriminately, have generated substantial changes, most of them very useful and positive, but others quite dangerous and deleterious. Mental and physical barriers have been broken, generating major transformations in our culture. Certainly, almost everything seems to be changing, but unfortunately not necessarily for good. We have become “citizens of the world,” and knowledge is now considered the most valuable trade. Along with this, though, many new problems have appeared. Individualism, super specialization and dehumanization are just a few of them. This “selfish culture” has the risk of auto self distraction. Today’s universities have not yet assumed the role they should in this new “Society of Knowledge.” It seems that the XXIth century’s universities, instead of helping resolve these problems, are in fact, contributing to them. Superior education has become overcrowded. This factor generates new problems by itself, such as the need to certify the quality of the new educational institutions. Employment availability has not expanded accordingly to the new graduates’ needs. This has reinforced individualism. Additionally, as technological investigation is now mainly coming from the business and industrial world in response to their particular interests, the university has lost leadership in this area. Essential changes should take place within this institution, to generate a positive change, a step up in the evolution towards a new society, where all human beings could have equal opportunities. The “magic formula” should include a holistic and multidisciplinary view of the world, introducing reflexion and core values and principles -not just from the theoretical but also from the practical point of view-. We should not only talk about core values; we should practice them in our daily routine, showing our students that these are the “tools” they should use and transmit to others, in order to make this world a better place to live. As members of the University Faculty, we are asked to assume a very important formative role. We should never forget that the ultimate mission of the university is to contribute in the development of a better society.